Survey and analysis of internal temperatures of Lebanese domestic refrigerators. (February 2015) - Hassan, Hussein F.; Dimassi, Hani; El Amin, Rafal
Abstract: In the light of power crisis that Lebanon is witnessing, temperatures were recorded, using data loggers, in 147 domestic refrigerators in three main cities every 5 min over 3 days. A questionnaire was administered to gather information on household characteristics, power supply and refrigerator. Temperatures were on average 8.0 °C with minimum −5.9 °C and maximum 37.0 °C. Income, number of household members, age, brand, load level and seal of the fridge, frequency of power cuts and availability of alternative power had no significant effect on the overall mean temperature, while the city and the distance to heat source had a significant effect. The number of high temperature readings ( T > 6 °C) differed significantly between the cities, while the availability of an alternative power was borderline significant. The lowest average temperatures were recorded during the night and 70% of average temperatures were in the danger zone (above 6 °C). This study can provide input to food safety risk assessments. Highlights: Temperature recordings ranged between −5.9 and 37 °C. Overall mean temperature was 8 °C & 71% of average temperatures were above 6 °C. Number of above 6 °C readings differed significantly between cities. Availability of alternative power was borderline significant for number of bad readings. 100% of surveyed fridges did not have a thermometer to check internal temperatures.